UMP Champion MTUN Treasurer Department Sports Carnival - Nor Salwana, Mohammad Idris (UMPSA, 2023)
PEKAN, 17 February 2023 – Universiti Malaysia Pahang (UMP), the host team, won the MTUN Treasurer Department Sports Carnival with nearly 150 Treasurer Department staff from four Malaysian Technical University Networks (MTUN) universities for two days recently.